THE ROLE OF CREATIVE ECONOMY IN IMPROVING SOCIAL WELFARE AMONG MILLENNIALS - Sari Mariahma Nova Sipayung; Ajeng Faizah Nijma Ilma (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
This study aims to examine the role of the creative economy in improving social welfare among the millennial generation through a literature review approach. The creative economy as a sector that relies on ideas, creativity, and innovation has great potential in creating inclusive and sustainable economic opportunities, especially for the younger generation. The millennial generation who are adaptive to technology and dynamic in their work make them the main actors in the development of the creative economy. Through a search of various scientific literature, articles, and policy reports, this study found that the creative economy not only contributes to economic growth, but also plays a role in expanding employment opportunities, increasing social participation, and strengthening cultural identity. In addition, the creative economy encourages millennials to become independent and innovative economic actors, which has a direct impact on improving social welfare both individually and as a community. These findings indicate that the development of a creative economy that is targeted and based on local potential can be an effective strategy in improving the quality of life of the millennial generation in Indonesia, especially in areas with high creative potential.